PERLINDUNGAN HUKUM TERHADAP PERAWAT YANG BEKERJA PADA MALAM HARI BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Lidya Destyani; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Since Indonesia was founded, the people of Indonesia have realized that work is a basic need of citizens. One of the job opportunities is offered to people who have specialist knowledge especially nursing and work in hospital. In his consideration, the authors took place at Aulia Hospital Pekanbaru, the caregiver was male and female. They are not entitled to such rights as set forth in the Manpower Act and other government regulations relating to protection, in particular the rights to be obtained for male and female nurses working at night.The purpose of this research is First, the implementation of legal protection against nurses who work at night at Aulia Hospital Pekanbaru based on Law Number 13 Year 2003 About Manpower. Second, constraints and efforts faced by the parties in the implementation of legal protection against nurses who work at night in Aulia Hospital Pekanbaru. This type of research is sociological research. This research was conducted at Aulia Hospital Pekanbaru. The population is the nursing manager and contract nurse. The data used are primary data and secondary data. Data collection techniques are interviews, questionnaires and literature study.From the results of research there are two things that can be concluded. First, the implementation of the legal protection of nurses who work at night in Aulia Hospital Pekanbaru is still not fulfilled, namely the right to get food and drink, the right to get security during work, and the right available shuttle facility workers. Secondly, the efforts and obstacles to fulfill the right of nurse, Aulia Hospital Pekanbaru's obstacle is the lack of understanding of the regulation in Law Number 13 Year 2003 on manpower so as not to explain in detail the right of nurse, the nurse does not know the right what they should get at work. It should make an agreement that contains all the rights and obligations of both applied during the employment relationship, until the workers know all of their rights that should be earned while working and the employers know their duties and what they should do to give the nurse right.Key Words: Legal protection of nurses at night, male nurses and female nurses - Aulia Hospital Pekanbaru Pekanbaru